Avaliação da tenacidade à fratura em juntas soldadas circunferenciais de tubulações de processo - Gumieri, Thierry Henrique Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This work aims to analyze the toughness of a welded joint in the presence of a crack through the analysis of maximum tension the material can withstand the presence of this type of defect, since a discontinuity is likely to occur in this type of joint and its detection and its design is simple, using non-destructive testing techniques. The study will be conducted through the CTOD test - Crack-Tip Opening Displacement, with type specimens SE (B) - Single Edge Bend taken from a weld in the L-C position in relation to the length (longitudinal axis) of a test tube. The main idea is to simulate the welding conditions for the manufacture of industrial pipes, made in boiler shops (pipe-shop) within petrochemical plants. These pipes are often subject to operation with flammable and toxic subjected to high pressures and temperatures, where one can break the line can cause irreparable damage to the plant, the environment and the health of surrounding communities. With this study we evaluate whether the weld metal has the same properties as fracture toughness of the base material. This study shows the importance of using a qualified welding procedure for performing quality welds while maintaining the properties of the fracture toughness of the base metal. It was found from the results of tests using a welding procedure described for carrying out welding ensures mechanical properties very close to the base metal, which in terms of design is great, since one can ensure that the weld will the same characteristics of the base metal specified for the assembly of the pipe

Este trabalho visa analisar a tenacidade de uma junta soldada na presença de uma trinca considerando a máxima tensão que o material pode suportar na presença desse tipo de defeito, visto que é uma descontinuidade comum de ocorrer nesse tipo de junta e sua detecção por meio de ensaios não destrutivos é simples, possibilitando inclusive seu dimensionamento. O estudo será realizado através do ensaio CTOD – Crack-Tip Opening Displacement, com corpos de prova tipo SE(B) – Single Edge Bend retirados de uma junta soldada e do metal base na posição L-C em relação ao plano do comprimento de um tubo de teste. A idéia principal é simular as condições de soldagem para a fabricação de tubulações industriais, realizadas em oficinas de caldeiraria (pipe-shop) dentro de plantas petroquímicas. Essas tubulações estão freqüentemente sujeitas à operação com produtos inflamáveis e tóxicos submetidos a grandes pressões e temperaturas, onde um possível rompimento da linha pode causar danos irreparáveis à planta industrial, ao meio ambiente e à saúde das comunidades vizinhas. Esse estudo apresenta a importância da utilização de um procedimento de soldagem qualificado para a realização de soldas de qualidade, mantendo as propriedades de tenacidade à fratura do metal de base
Keywords: Mecanica da fratura; Juntas soldadas